Estimating Iceland's Real Equilibrium Exchange Rate - Tchaidze, Robert (IMF Working Papers; Working Paper ;, 2007)
Given recent developments in Iceland, this paper evaluates its real exchange rate disequilibrium. It discusses three approaches to estimating the equilibrium values and suggests that the adjustment needed to bring the real exchange rate in line with fundamentals is in the range of 15-25 percent, although timing and manner of this adjustment is unclear.